2023
DOI: 10.1007/s11661-023-07177-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Pressure and Substrate Bias Voltage on Structure and Mechanical Properties of Vacuum Arc Deposited VN Coatings

A. S. Kuprin,
A. Gilewicz,
G. N. Tolmachova
et al.

Abstract: The binary vanadium–nitrogen (V–N) coatings were formed using cathodic arc evaporation. Two sets of coatings were produced using: (a) nitrogen pressure (pN2) from 0.001 Pa to 3 Pa at a constant substrate bias voltage (UB) of − 100 V and (b) a substrate bias voltage from − 50 to − 300 V at a constant nitrogen pressure of 1.5 Pa. The influence of the above parameters on the coating properties, in particular on the insufficiently investigated and described adhesion of the coatings to the substrate, was demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…At 20% N 2 partial pressure, a prominent diffraction peak corresponding to FCC-VN phase with (220) as crystalline plane is detected, along with minor (111) and (200) peaks. This suggests the presence of VN at 20% N 2 partial pressures, the absence of pure V indicates conversion of V to VN by filling interstitial sites with nitrogen atoms, in line with the observations made by Kuprin et al [27]. Coatings deposited at N 2 partial pressures of 40%, 60%, and 80% all exhibited the FCC-VN phase, characterized by a prominent peak at the (200) plane.…”
Section: Microstructure Analysissupporting
confidence: 89%
“…At 20% N 2 partial pressure, a prominent diffraction peak corresponding to FCC-VN phase with (220) as crystalline plane is detected, along with minor (111) and (200) peaks. This suggests the presence of VN at 20% N 2 partial pressures, the absence of pure V indicates conversion of V to VN by filling interstitial sites with nitrogen atoms, in line with the observations made by Kuprin et al [27]. Coatings deposited at N 2 partial pressures of 40%, 60%, and 80% all exhibited the FCC-VN phase, characterized by a prominent peak at the (200) plane.…”
Section: Microstructure Analysissupporting
confidence: 89%
“…Other reflections of this phase (001) and ( 101) are much weaker in the diffractograms, and reflections (110), (002), ( 111), (102) are not detected at all, which is due to the formation of a sufficiently strong axial texture with a predominant orientation of crystallites with planes (h00) parallel to the surface of the sample, i.e., the location of the crystal lattice hexagons with the c-axis in the coating plane. A similar arrangement of hexagons was previously observed in α-Ti vacuum-arc coatings [32], but in h-VN coatings, the predominant orientation of crystallites was found to be with the base planes (00l), i.e., the c-axis perpendicular to the surface [33]. The phase identification was performed according to the International Centre for Diffraction Data (ICDD) pattern.…”
Section: Chemical and Phase Compositionmentioning
confidence: 70%
“…The coating formed without nitrogen is characterized by a hexagonal structure, and the addition of oxygen changes the structure to a cubic one, Figure 5. Previous studies have shown that the hexagonal vanadium nitride coating is characterized by higher hardness than the coating with a cubic structure [33,51].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations